2003
DOI: 10.1177/002215540305100902
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Angiogenesis in Aging Is Associated with Alterations in Vessel Density, Matrix Composition, Inflammatory Response, and Growth Factor Expression

Abstract: It is generally accepted that angiogenesis is delayed in aging. To define the effects of age on the neovascular response, polyvinyl alcohol sponges were implanted SC in young (6-8 months old, n ϭ 11) and aged (23-25 months old, n ϭ 13) mice and sampled at 14 and 19 days. Angiogenic invasion was significantly delayed in aged mice at 14d relative to young at 14d (% area of invasion 9.0 Ϯ 3.7 vs 19.0 Ϯ 5.6; p ϭ 0.02). Although microvessel morphology and basement membrane composition were similar between the age g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
125
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 146 publications
(137 citation statements)
references
References 43 publications
9
125
0
3
Order By: Relevance
“…Recent studies have demonstrated provocative linkage between age, cardiovascular disease, and insufficiency of HIF-1 expression in both ischemic tissues and infiltrating myeloid cells (55,56). Because aging can also impair induction of VEGF expression (57,58), our work suggests that therapeutic angiogenesis may require combinatorial restoration or administration of both HIF-1 and VEGF to achieve optimal tissue neovascularization.…”
Section: Discussionmentioning
confidence: 77%
“…Recent studies have demonstrated provocative linkage between age, cardiovascular disease, and insufficiency of HIF-1 expression in both ischemic tissues and infiltrating myeloid cells (55,56). Because aging can also impair induction of VEGF expression (57,58), our work suggests that therapeutic angiogenesis may require combinatorial restoration or administration of both HIF-1 and VEGF to achieve optimal tissue neovascularization.…”
Section: Discussionmentioning
confidence: 77%
“…Likewise, the numbers of capillaries per muscle fiber in young p75KO and old WT mice were significantly lower than in young WT mice. These data strongly suggest that age-associated decrease in angiogenesis 22,27,28 is, at least in part, a result of impaired signaling through TNFR2/p75. Aging is associated with increased expression of p55 and decreased expression of p75 in human cells 12 and a decrease in the expression of p75 receptor in PB EPCs from adult donors.…”
Section: Goukassian Et Al Tnfr2/p75 and Neovascularization 759mentioning
confidence: 79%
“…In brief, early EPCs in the bone marrow or immediately after their migration into the systemic circulation are positive for AC133/CD34/VEGFR-2, whereas circulating EPCs are positive for CD34/VEGFR-2/CD31/VEcadherin and lose AC133. 15,[26][27][28] Murine bone marrow transplant (BMT) experiments have demonstrated the incorporation of bone marrow-derived EPCs into foci of physiological and pathological neovascularization. 18 Mice lethally irradiated and transplanted with bone marrow harvested from transgenic donors constitutively express a fluorescent LacZ probe which is regulated by an endothelial cell-specific promoter, for example, Flk-1 (VEGF receptor) or Tie-2(angiotensin-2 receptor).…”
Section: Discussionmentioning
confidence: 99%
“…These include diabetes mellitius, [7][8][9][10] hypercholesterolaemia, 11 smoking, 12,13 and advancing age. 14,15 The recent recognition that vasculogenesis, a process by which bone marrow stem cells committed to the vascular endothelial lineage, termed endothelial precursor cells (EPC), can migrate from bone marrow to a developing neovasculature, in adults, has stimulated much interest. [16][17][18] This was previously believed to be an exclusively embryonic process.…”
Section: Introductionmentioning
confidence: 99%